Розрахунок просторового розподілу концентрації бінарної суміші в зовнішньому полі - Булавін, Л.А.; Гаврюшенко, Д.А.; Сисоєв, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
The liquid lattice model has been examined to calculate a binary solution component concentration. The external field potential expansion in a functional Taylor series has been constructed to obtain the expansion in direct correlation functions of all orders. The quantitative criteria for the expression to be applied have been indicated. The expansion of the binary solution
concentration in a functional Taylor series has been obtained to gain an expansion in correlation functions of all orders. A solution of the differential equation for a plane-parallel pore with an exponential wall potential has been obtained.